2007
DOI: 10.1002/hbm.20343
|View full text |Cite
|
Sign up to set email alerts
|

Covariations among fMRI, skin conductance, and behavioral data during processing of concealed information

Abstract: Imaging techniques have been used to elucidate the neural correlates that underlie deception. The scientifically best understood paradigm for the detection of deception, however, the guilty knowledge test (GKT), was rarely used in imaging studies. By transferring a GKT-paradigm to a functional magnetic resonance imaging (fMRI) study, while additionally quantifying reaction times and skin conductance responses (SCRs), this study aimed at identifying the neural correlates of the behavioral and electrodermal resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
90
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 65 publications
9
90
0
Order By: Relevance
“…The presence of guilty knowledge in all these fMRI studies was revealed by comparing the brain activity elicited by probe, target, and irrelevant stimulus categories. In contrast to the studies of Instructed Lies reviewed above, which only infrequently found activation of DLPFC areas associated with working memory function, most GKT studies report DLPFC activation (Langleben et al, 2002(Langleben et al, , 2005Kozel et al, 2005Kozel et al, , 2009aPhan et al, 2005;Gamer et al, 2007;Hakun et al, 2008;Monteleone et al, 2009;Nose et al, 2009). Overall, these fMRI GKT studies are also characterized by more consistent activations in brain areas associated with executive processes.…”
Section: Hemodynamic Results In Gkt Experimentsmentioning
confidence: 60%
“…The presence of guilty knowledge in all these fMRI studies was revealed by comparing the brain activity elicited by probe, target, and irrelevant stimulus categories. In contrast to the studies of Instructed Lies reviewed above, which only infrequently found activation of DLPFC areas associated with working memory function, most GKT studies report DLPFC activation (Langleben et al, 2002(Langleben et al, , 2005Kozel et al, 2005Kozel et al, , 2009aPhan et al, 2005;Gamer et al, 2007;Hakun et al, 2008;Monteleone et al, 2009;Nose et al, 2009). Overall, these fMRI GKT studies are also characterized by more consistent activations in brain areas associated with executive processes.…”
Section: Hemodynamic Results In Gkt Experimentsmentioning
confidence: 60%
“…Although the CIT is not a test of deception, it was reasoned that the denial of relevant-item knowledge causes a conflict between the truthful and the required deceptive response, which is resolved by inhibiting the former response (Seymour & Schumacher, 2009;Verschuere & De Houwer, 2011). Response inhibition has been indicated to play a role in the CIT based on Reaction Time (Suchotzki, Verschuere, Peth, Crombez, & Gamer, 2014) and fMRI measures (e.g., Gamer, 2014;Gamer, Bauermann, Stoeter, & Vossel, 2007;Langleben et al, 2002;Phan et al, 2005), but it remains unclear whether it plays a role in the autonomic-based CIT (see Ambach, Stark, Peper, & Vaitl, 2008a;Ambach et al, 2011). Indeed, meta-analytic studies have demonstrated that similar CIT effects were observed with the SCR measure when subjects responded deceptively to the relevant items and when they remained silent and did not give any overt responses (Ben-Shakhar & Elaad, 2003;Meijer, klein Selle, Elber, & Ben-Shakhar, 2014).…”
mentioning
confidence: 99%
“…Importantly, changes in EDA appear to be positively related to patterns of neural activation, particularly within the prefrontal cortex during memory and attentional tasks. [27][28][29] For this measure to be used in future investigations of concussion, however, typical responses first need to be quantified. To do so, we measured EDA in individuals with or without a history of concussion during administration of the Standardized Assessment of Concussion (SAC)-a valid and reliable clinical test of cognitive status often used as a baseline measure and after concussion.…”
mentioning
confidence: 99%